“He is sent to this place, and good will result to the cause of God”: Young Richard Preston, Race, and Religion in Early-19th-Century Nova Scotia - Grant, Keith S. (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2024)
Reverend Richard Preston (c. 1791-1861), formerly enslaved in Virginia, looms large in African Nova Scotian history for his role as a pastor, abolitionist, community organizer, and founder of the African Baptist Association. During a largely forgotten early episode in his career, in 1823-1824, Preston preached in the Annapolis Valley and sparked an extensive religious revival. Unlike much of his later public ministry, Preston preached to racially integrated or predominantly white audiences. His ministry elicited a range of responses, from curiosity and conversion to insidious prejudice and outright hostility, conveying the complex relationships between race and religion in early-19th-century Nova Scotia.